Corruption: Working Hasn’t Completed - Gde Made Swardhana; I Nyoman Sukandia (Fakultas Hukum, Universitas Warmadewa, 2020)
This article discusses problems of corruption which until now hasn’t been completed in its eradication process. Every effort is made to find both internal and external causes in order to get the solution. The problem that is studied sociologically is, why is corruption incomplete? If corruption isn’t yet complete, and work isn’t finished yet, then how can work be completed? Understanding Corruption can be called work is complete, must be understood from the anti-corruption values and principles contained therein. It’s include honesty, independence, discipline, responsibility, hard work, simple, courage, and justice. It’s need to be applied by each individual to be able to overcome external factors so that corruption doesn’t occur. To prevent the occurrence of external factors, in addition to having it, each individual needs to deeply understand the anti-corruption principles of accountability, transparency, fairness, policy, and policy control. Therefore the relationship between anti-corruption principles and values is an inseparable unity. Success or failure to solve the problem of corruption is expected in the legal system that makes the handle in solving corruption cases, namely strengthening the legal structure, legal substance and legal culture of the community.